Types of injuries caused by isolated electric scooter accidents - Kyongwon Yoo; Hyung Il Kim (Journal of Trauma and Injury)
Purpose The recent increase in electric scooter (e-scooter) use has been accompanied by an increase in injuries from e-scooter–related accidents. Studies have reported that most such injuries are minor, and physicians may therefore underestimate the severity of such injuries. This study investigated the types and severity of injuries caused by isolated e-scooter accidents (i.e., those that did not involve colliding with other cars or falling from heights). Methods This prospective observational study was conducted from May to December 2021 at Dankook University Hospital tertiary medical center. The demographic data of patients injured in isolated e-scooter–related accidents were collected. All injuries were categorized by body part. Results Fifty eligible patients visited our emergency department during the study period. Of these, 76% were categorized as nonemergency, and 62% were discharged after initial evaluation and treatment at the emergency department. Another 10% were admitted to the intensive care unit (ICU) and 18% to the ward, with nine patients receiving at least one operation. The average hospital stays were 2.4 days in the ICU and 9 days in the ward. One death occurred due to traumatic brain injury (overall mortality rate, 2%). Multiple fractures of the left third through ninth ribs combined with lung laceration and fractures of T12 and L4 were noted. Conclusions Various types and severities of injuries can occur in isolated e-scooter accidents. While most such injuries are minor, some will require ICU admission or surgery, and deaths can occur. Physicians should not underestimate the severity of such injuries.